Nursesâ burnout and counterproductive work behavior in a Nigerian sample: The moderating role of emotional intelligence - Leonard I. Ugwu; Ibeawuchi K. Enwereuzor; Udeagha S. Fimber; Dorothy I. Ugwu (Elsevier, 2017)
This study examined the moderating role of EI in the relationship between burnout and CWB among 401 nurses drawn from various hospitals within South-eastern Nigeria. Three instruments were used for the collection of data, namely: Counterproductive Work Behaviour Checklist, Maslach Burnout Inventory, and Brief Emotional Intelligence scale. Moderated multiple regression results showed that emotional exhaustion, depersonalization, and personal accomplishment, positively predicted CWB. In addition, EI significantly and negatively predicted CWB. Results also showed that EI moderated the positive relationship between emotional exhaustion and CWB and between depersonalization and CWB such that the positive relationship between these two dimensions of burnout and CWB was stronger for nurses with low EI compared to those with high EI. The implications of the findings and limitations of the study were discussed. Keywords: Nurses, Burnout, Counterproductive work behaviour, Emotional intelligence